Impact of PSP Technique on Clinical Outcomes Following Bioresorbable Scaffolds Implantation - Luis Ortega-Paz (Journal of Clinical Medicine, 2018)
Bioresorbable scaffolds (BRS) were introduced in clinical practice to overcome the long-term limitations of newer-generation drug-eluting stents. Despite some initial promising results of the Absorb BRS, safety concerns have led to the discontinuation of the commercialization of this device. Several retrospective studies have assessed the impact of the so-called Pre-dilation, Sizing and Post-dilation (PSP) technique concluding that an optimal PSP technique can improve clinical outcomes following BRS implantation. In this article, the definition of the PSP technique, and the current evidence of its impact on clinical outcomes are put in perspective. Additionality, the relationship between the PSP technique and the dual-antiplatelet therapy to prevent scaffold thrombosis is addressed. Finally, the future perspectives of BRS technology in clinical practice are commented.